INTERAKSIONISME SIMBOLIK BUDAYA DAN AGAMA : (Studi Pada Ikon Kabupaten dan Kota Pekalongan) - Nazhifah; Shulkha Kamilia; Riska Auliyani; Rizki Muhammad Rafi (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2024)
This study aims to determine the cultural and religious meaning contained in an icon in the district and city of Pekalongan. This study is a study using a descriptive qualitative method with a socio-historical approach. Data collection techniques used in this study are observation, interviews, and documentation. The results of this study, the author shows that the icon in Pekalongan Regency is a three-dimensional Al-Qur'an and the icon in Pekalongan City is the Archipelago Gate. The existence of these icons is influenced by the religious conditions of the community in each region. The district is represented that the community is Santri, so the term Santri City is known in Pekalongan Regency. While the city, represents that the community is a batik businessman, so the term Batik City is known in Pekalongan City. Therefore, these two icons greatly shape each of Pekalongan's cultural identities, namely batik, painting, and the religious cultural identity of santri studying the Koran. Therefore, these two icons not only function as physical representations of the city and district, but also as religious symbolism and cultural identity that reflects the richness and diversity of the Pekalongan community.